2017
DOI: 10.1007/s10103-017-2160-7
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation laser and pulsed electrical field increase the viability of the musculocutaneous flap in diabetic rats

Abstract: The purpose of this study is to investigate the effect of pulsed electrical field (PEF) and photobiomodulation laser (PBM) on the viability of the TRAM flap in diabetic rats. Fifty Wistar rats were divided into five homogeneous groups: Group 1-control; Group 2-diabetics; Group 3-diabetics + PEF; Group 4-diabetic + laser 660 nm, 10 J/cm, 0.27 J; Group 5-diabetic + laser 660 nm, 140 J/cm, 3.9 J. The percentage of necrotic area was evaluated using software Image J®. The peripheral circulation of the flap was eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…Although the results of the epidermis presented greater thickness in the group that received 658 nm of radiation, the results were not significant in the epidermis between the groups that received the different wavelengths of the laser therapy or the control group. Conflicting with these results, studies have noted a greater re-epithelialization of the epidermis after applying laser wavelengths between 808 nm to 830 nm in immunosuppressed [18] and diabetic animals [39]. Moreover, Leite et al [39] observed positive results of increased epidermal thickness in radicular cutaneous flap with 660 nm laser therapy with fluency of 140 J/cm 2 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the results of the epidermis presented greater thickness in the group that received 658 nm of radiation, the results were not significant in the epidermis between the groups that received the different wavelengths of the laser therapy or the control group. Conflicting with these results, studies have noted a greater re-epithelialization of the epidermis after applying laser wavelengths between 808 nm to 830 nm in immunosuppressed [18] and diabetic animals [39]. Moreover, Leite et al [39] observed positive results of increased epidermal thickness in radicular cutaneous flap with 660 nm laser therapy with fluency of 140 J/cm 2 .…”
Section: Discussionmentioning
confidence: 98%
“…Conflicting with these results, studies have noted a greater re-epithelialization of the epidermis after applying laser wavelengths between 808 nm to 830 nm in immunosuppressed [18] and diabetic animals [39]. Moreover, Leite et al [39] observed positive results of increased epidermal thickness in radicular cutaneous flap with 660 nm laser therapy with fluency of 140 J/cm 2 . Different animal models and different wavelength and fluency must explain the different effect observed in this work.…”
Section: Discussionmentioning
confidence: 98%
“…Dessa forma, podem gerar modificações na função e forma da célula, migração e sinalização celular, agindo nas fases da cicatrização, acelerando o processo (DE ALENCAR et al, 2018) Estudos clínicos e experimentais mostram que a fotobiomodulação com comprimento de onda que vão desde do espectro vermelho ao infravermelho (600 -1000 nm), promove a reparação tecidual de feridas crônicas (LANDAU et al, 2011;MATHUR et al, 2017;VITSE et al, 2017), estimulam a angiogênese (CORAZZA et al, 2007;PARK et al, 2015) e síntese de colágeno (LAU et al, 2015), modulam as reações inflamatórias e a proliferação de fibroblastos (XAVIER et al, 2010;SHARIFIAN et al, 2013). Também aumentam a espessura da epiderme, reduz a área de necrose e aumenta o fator de crescimento do endotélio vascular (LEITE et al, 2017).…”
Section: Lista De Tabelasunclassified